Measurement of the ratio of branching fractions of the Upsilon(4S) to charged and neutral B mesons - Athar, S; Avery, P; Stoeck, H; Yelton, J; Brandenburg, G; Ershov, A; Kim, D; Wilson, R; Benslama, K; Eisenstein, B; Ernst, J; Gollin, G; et al. (2002)
The ratio of charged and neutral B meson production at the γ(4S), f +-/f 00, is measured through the decays B̄→D*ℓ -ν̄ ℓ, reconstructed using a partial reconstruction method where the D* is detected only through a pion daughter from the decay D*→Dπ. Using data collected by the CLEO II detector, the charged and neutral B decays are measured in such a way that their ratio is independent of the decay model, limited mainly by the uncertainty in the relative efficiency for detecting neutral and charged pions. This measurement yields the ratio of production fractions times the ratio of semileptonic branching fractions, f +-b +/f 00b 0. Assuming that b +/b 0 is equal to the lifetime ratio τ +/τ 0 and using the world average value of τ +/τ 0 as input, we obtain f +-/f 00= 1.058±0.084±0.136. © 2002 The American Physical Society.